Reinterpretation of Hadiths on Religious Moderation: A Maqāṣidī Al-Sharīʿah Perspective - Zulfa Rizal; Nabilah Yusof; Muhammad Abdul Kharis (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2025)
This study examines hadiths concerning religious moderation through a maqāṣid al-sharī'ah framework in the context of contemporary interreligious relations. Despite extensive hadith scholarship, few studies systematically apply the maqāṣid framework to moderation discourse, especially in addressing religious extremism rooted in literalist interpretations that overlook Islamic law's normative objectives. Employing a thematic (mawḍū'ī) method, this study analyses hadiths from Ṣaḥīḥayn and al-Sunan al-Arba'ah concerning tolerance, the prohibition of ghuluw (excessiveness), and the Prophet Muhammad's interfaith practices. Al-Shāṭibī's maqāṣid framework serves as the interpretive lens, focusing on the protection of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), and human dignity. The findings show three guiding principles: rejecting religious extremism (ghuluw), putting ease (taysīr) over difficulty, and accepting religious pluralism as a normal part of life. This study is the initial effort to implement al-Shāṭibī's classical framework for contemporary interfaith ethics, which illustrates that religious moderation in hadith transcends doctrinal mandates to provide contextual ethical-operational guidance. The research offers a maqāṣid-based hermeneutical paradigm that bridges scriptural authenticity with plural social realities, equipping Islamic scholars, policymakers, and interfaith practitioners with methodological tools to counter extremism and develop inclusive public theology in religiously diverse societies.